Rheological properties of mozzarella cheese determined by creep/recovery tests: Effect of sampling direction, test temperature and ripening time - Olivares, María Laura (2009)
The viscoelastic properties of mozzarella cheese using a creep/recovery test considering different sampling directions (parallel and perpendicular to protein fiber orientation), test temperatures (20, 30 and 40C) and ripening times (1, 8, 15, 29 and 36 days) were studied. Creep data were interpreted by a Burger model of four parameters. A semiempirical approach was proposed to obtain the contribution of each main compliance to the total deformation of the system. Creep tests at different temperatures allowed gaining a better understanding of changes that occur in the cheese matrix during heating and ripening. Sampling direction did not affect any of the parameters studied. Finally, it was clearly observed that cheese matrix behaves as a quite different physicochemical system depending on temperature. Therefore, it is recommended to carry out the rheological tests at different temperatures to evaluate appropriately the viscoelastic properties of mozzarella cheese.